2021
DOI: 10.3389/fcell.2021.720110
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Images and Multi-Omics Integration Predict Molecular Characteristics and Survival in Lung Adenocarcinoma

Abstract: Histopathological images and omics profiles play important roles in prognosis of cancer patients. Here, we extracted quantitative features from histopathological images to predict molecular characteristics and prognosis, and integrated image features with mutations, transcriptomics, and proteomics data for prognosis prediction in lung adenocarcinoma (LUAD). Patients obtained from The Cancer Genome Atlas (TCGA) were divided into training set (n = 235) and test set (n = 235). We developed machine learning models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…However, native ML models cannot handle time-to-event data while accommodating censored observations. Reflecting this, we found that ML studies predicting NSCLC/LAD survival mainly formulated the survival analysis as a classification problem and transformed time-to-event data into dichotomized endpoints ( 90 94 , 96 , 100 , 102 , 103 , 106 , 108 111 , 113 , 116 , 117 , 134 , 135 ). To this end, utilizing Random Survival Forests (RSF) for continuous time-to-event survival prediction and those aiming to identify optimal time-to-event ML models were emerging ( 98 , 99 , 101 , 105 ), but further applications and research in this area are warranted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, native ML models cannot handle time-to-event data while accommodating censored observations. Reflecting this, we found that ML studies predicting NSCLC/LAD survival mainly formulated the survival analysis as a classification problem and transformed time-to-event data into dichotomized endpoints ( 90 94 , 96 , 100 , 102 , 103 , 106 , 108 111 , 113 , 116 , 117 , 134 , 135 ). To this end, utilizing Random Survival Forests (RSF) for continuous time-to-event survival prediction and those aiming to identify optimal time-to-event ML models were emerging ( 98 , 99 , 101 , 105 ), but further applications and research in this area are warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Under the surrogate biomarker category, we identified 60 ML studies ( Table S1I ). The top predicted biomarkers were EGFR mutation status ( 44 , 58 , 183 209 ), PD-L1 expression status ( 190 , 210 215 ), ALK mutation status ( 94 , 216 219 ), KRAS mutation status ( 44 , 194 , 197 , 220 ), and TMB subtype ( 221 223 ) ( Figures 4D, E ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the analysis results for TCGA HNSCC, TCGA LUAD, and TCGA BRCA data are provided in supplementary materials . Note that we take the published biomarker genes ( GIMAP6, SELL, TIFAB, KCNA3, CCR4 ) related to HNSCC ( Ran et al, 2021 ); ( ALK, BRAF, EGFR, ROS1 ) related to LUAD ( Chen et al, 2021 ); ( TMEM190, TUBA3D, LYVE1, LILBR5, CD209 ) related to BRCA ( Liu et al, 2019 ) as a survival prediction model to make comparisons. We identify nine genes and find the four genes ( PITPNM3 , MXD4 , ABCB1 , BATF ) that are related to HNSCC in the literature ( Aravind et al, 2021 ; Wu et al, 2019b ; da Silva et al, 2021 ; Duz & Karatas, 2021 ; Wang et al, 2020 ; and Wen et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many histopathological biomarkers have been developed for the prognosis of patients with lung cancer. For instance, Yu et al [ 13 ] and Chen et al [ 24 ] employed CellProfiler [ 25 27 ] software to quantitatively measure cellular phenotypes in histopathological images, and correlated these features with prognosis. Several studies [ 28 30 ] captured cellular-level feature descriptors from segmented nuclei for predicting prognosis in early-stage non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%